My Distant Acquaintance with Philosopher-Physician Nikolaos Louros and my Intimate Engagement with His Archives - Tselikas, Agamemnon (DELTOS, 2024)
Five letters exchanged between Nikolaos Louros, the medical doctor, academician, philosopher, and renowned men of letters during the 1963-1966 years, are presented in this article. The topic of all these letters was the Louros’ decision to use in his voluminous book “Obstetrics and Gynaecology” the vernacular Greek language instead of the formal “Katharevousa” an artificial language imposed on the newly formed Greek State by the middle of the 19th century by the then archaephile literati. Their aim was initially applauded as a means to “purify” the language suffering of the many local dialects and the “barbarism” of the mass of uneducated Greeks. However, as time passed, it became an obstacle to expression and free thinking. The establishment, particularly the medical one, insisted upon its use in the University and the texts written by the faculty members. Thus, it required a lot of courage by Nikolaos Louros to use for the first time the vernacular in a scientific medical book. The opportunity to present these epistles was given by my friend Professor Athanasios Diamandopoulos, who classified Louros’ huge Archive wherein, between a lot of other letters, those five ones were traced. These include two between the academician novelist Elias Venezis (1963), two more with the philosopher Evangelos Papanoutsos (1963) and one with the intellectual author Kostis Bastias (1966). The spirit of all of five letters underlines the overwhelming acceptance by the recipients of Louros’ ideas about the language. They accept the real contribution of the vernacular to a better understanding by medical students the substance of Louros’ book which would be otherwise obscured by the bounds of “katharevousa” The article concludes with the memories of the author ‘s acquaintance with Louros while the former was in his green days in paleography and Louros already was a respectable member of the echelons in the academic and social life.